ENSURING THE QUALITY OF ENGINEERING TRAINING FOR THE AUTOMOBILE AND ROAD-CONSTRUCTION COMPLEX OF RUSSIA - Viktor V. Ushakov (Высшее образование в России, 2016)
The article focuses on the organization at MADI of competency-based education system with modular learning process. The transition to two-tier education system entails the introduction of education programs of a new generation, the improvement of methodical provision and quality management system, establishment of new forms ofinteraction between university and employers. Special attention is paid to the organization of basic enterprise affiliated chairs where the practice-oriented programs are applied. These chairs contribute significantly to the development of target training of specialists on the basis of individual curricula. The author shows the university achievements in implementing computer testing systems to control the education quality. The article also highlights the international activities of MADI, particularly the realization of TEMPUS HDMCuRF proj ect and implementation of HDM master courses.